DAMPAK PENGEMBANGAN PARIWISATA BANTO ROYO TERHADAP KONDISI SOSIAL EKONOMI DAN LINGKUNGAN MASYARAKAT NAGARI KOTO TANGAH KECAMATAN TILATANG KAMANG - Fajri Febrian; Widya Prarikeslan (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study aims to determine the impact of Banto Royo tourism development on people's lives in terms of economic conditions, social conditions and environmental conditions. This type of research is descriptive with a quantitative approach. The population in this study are people who work at the Banto Royo tourist attraction. Sampling was done by total sampling method with a sample size of 63 respondents. Data collection techniques through questionnaires and documentation and data analysis using percentage techniques. The results of this study indicate that the development of Banto Royo tourism is able to have an impact on: 1) Economy, the impact in the form of changes in income has increased (100%) from the previous conditions and job opportunities have become easier (39, 7%). 2) Social, the impact is in the form of changes in livelihoods (50, 8%), good interaction relations, low social deviation (58.7%) and increased social mobility (74, 6%). 3) Environment, the impact is in the form of clean environmental conditions (74.6%), and increased waste conditions (47.6%) but can be managed properly (65.1%).